Factors affecting the translation, interpretation, and extrapolation abilities in elementary school students' learning achievement - Sri Wuryanti; Deni Hadiana; Rumondang Purwati (Graduate School, Universitas Negeri Yogyakarta, 2020)
This study was to determine the correlation between translation, interpretation, and extrapolation abilities on the learning achievement of elementary school students in science subjects. The research method was descriptive quantitative. Data collection techniques used tests to understand the concepts of translation, interpretation, and extrapolation with test techniques and students’ learning achievement with secondary data. Product moment and regression test were used in data analysis. The research results show that (1) there is a correlation between translation ability and the level of science learning achievement of grade V students; the significance level is satisfactory. (2) There is a correlation between the interpretation ability and the level of science learning achievement of grade V students; the significance level is satisfactory. (3) There is a correlation between extrapolation ability and the level of science learning achievement of grade V students; the significance level is very satisfactory. (4) There is a correlation between the ability of translation, interpretation, and extrapolation on the science learning achievement of grade V students; the level of significance is very satisfactory.